IMPLEMENTATION OF THE 5 CHARACTER FLOWERS PROGRAM IN IMPROVING THE CHARACTER OF LEARNERS IN PUBLIC ELEMENTARY SCHOOLS IN PURWAKARTA DISTRICT - Rakhmah, Pipih Soviyatin; Rahyasih, Yayah; Sudarsyah, Asep (Universitas Negeri Medan, 2024)
This study aims to examine the implementation of the 5 Flowers of Character program in improving the character of students in public elementary schools in Purwakarta Regency. This program is a character education initiative implemented at the elementary school level to shape students' positive personality and behavior. The research method used is qualitative, with data collection through observation, interviews, and documentation studies in seven public primary schools in Purwakarta District, namely SDN 1 Nagrikidul, SDN 1 Sinkas, SDN 1 Cipaisan, SDN 8 Nagrikaler, SDN 1 Nagrikaler, SDN 6 Ciseureuh, and SDN 1 Munjuljaya. The results show that the 5 Flowers of Character program has been implemented with various variations in each school. In general, the program focuses on developing five main character values represented by five types of flowers. The program implementation involves the integration of character values in the curriculum, extracurricular activities and school culture. Challenges faced in the implementation of the program include limited resources, diverse teacher understanding, and difficulties in measuring concrete character changes. Nevertheless, this study found that the 5 Flowers of Character program had a positive impact on students' behaviour and attitudes. Character improvement is seen in the aspects of discipline, responsibility, social care, and environmental awareness. The key success factors of this program are the support from the principal, the active involvement of teachers, and the participation of parents in strengthening character values at home. This study concludes that the 5 Flowers of Character program is an effective approach in shaping the character of students in elementary schools. Recommendations for future program development include improving teacher training, strengthening collaboration with parents, and developing more comprehensive evaluation methods to measure the impact of the program on learners' character.